Type of muscle control in elite alpine skiing - Kröll, J.; Spörri, J.; Fasel, B.; Schwameder, H.; Müller, E. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The main purpose of the lecture will be to compare the data from Berg et al. (1995, 1999) with current giant slalom data with respect to muscle control. Furthermore, a comparison of two different ski snow interaction modes will be provided. Based on the recent changes of FIS equipment rules, ski side cut radii with 27m were compared to ski side cut radii with 35m. Ski ground reaction forces, kinematics (knee and hip joint angle) and lower limb muscle activity (EMG) were determined simultaneously to draw a relative complex description on muscle control. In general a predominance of slow-velocity lengthening contractions of the quadriceps muscle group can be observed (as expected) when using current equipment. Additionally the new data reveals distinct features of specific muscles, which should help to find adequate (eccentric) exercise modes for alpine ski racers. Moreover, the new data potentially also strengthen the general understanding of ski-snow-human interaction on the other hand.